Water quality. Biological methods. Evaluation in an aqueous medium of the 'ultimate' aerobic biodegradability of organic compounds: method by analysis of dissolved organic carbon (DOC) Part 5-5.6, (31st December 1985) - British Standards Institution,
No abstract available